2021
DOI: 10.1371/journal.pone.0257600
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of the National Guidelines for Diagnosis and Treatment of Malaria among medical doctors in Ebonyi state, Nigeria: A cross-sectional survey

Abstract: Background The Guidelines for Diagnosis and Treatment of Malaria are meant to guide medical practitioners to enhance optimal management of patients suspected of having malaria which is vital to malarial control and elimination. Medical doctors have the main responsibility for treating patients with malaria so there was need to evaluate the extent to which the medical doctors in Ebonyi state, Nigeria, knew, viewed, and practiced the 2015 National Guidelines for Diagnosis and Treatment of Malaria. Methods A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…However, there was misconception with regard to the vector that transmitted malaria as only 1 to 3rd of the respondents selected mosquitoes as a pathogen vector for malaria. The findings of this study lend credence to those found in earlier research carried out in Nigeria, [23,34,35] Guinea, [28] Tanzania, [29] Ethiopia, [36] and India. [24]…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, there was misconception with regard to the vector that transmitted malaria as only 1 to 3rd of the respondents selected mosquitoes as a pathogen vector for malaria. The findings of this study lend credence to those found in earlier research carried out in Nigeria, [23,34,35] Guinea, [28] Tanzania, [29] Ethiopia, [36] and India. [24]…”
Section: Discussionsupporting
confidence: 89%
“…The structured questionnaire included demographic characteristics in the first part (nationality, gender, social status, number of family members, income, education level, type of accommodation, and area). The second part contained questions about knowledge, attitudes, and practices, which were designed based on previous studies [4,[22][23][24][25][26][27][28][29][30] and World Health Organization guidelines. [2,11,15] The knowledge questions were about the causes of malaria, the primary vector, symptoms, preventive measures, personal means for prevention, and knowledge about mosquito behavior.…”
Section: Study Measures and Questionnaire Designmentioning
confidence: 99%
“…The finding that duration of practice was significantly associated with respondents' knowledge about asymptomatic malaria transmission, and HCWs with 0-5 years of practice were less likely to be informed about asymptomatic malaria transmission compared to those with more years of practice, is expected, as HCWs may naturally gain more awareness, experience, and learn more about the condition with an increased number of years of practice. However, these findings were different from the results in Ebonyi State, Nigeria, where the number of years of practice was not significantly associated with doctors' knowledge of the national guidelines of malaria diagnosis and treatment [67]. The results showed that the proportion of correct respondents in rural hospitals was higher than that in the urban hospitals in all the assessment areas, which might be because most of the respondents in the rural hospitals were physicians (46%) (with only 18% being nursing assistants), while most of the respondents in the urban hospital were nursing assistants (34%).…”
Section: Knowledge Of Asymptomatic Malaria Among Health Care Workerscontrasting
confidence: 99%
“…Compared with the 68.0% in this study, a much lower proportion of 27.5% of the medical doctors in Ebonyi state were reported to never or rarely prescribed anti-malarial drugs for patients with negative MRDT results [ 45 ]. This much lower value could be due to the fact that the medical doctors (across tertiary and secondary health facilities), in most cases, believed in using their clinical judgement and discretion with less compliance to the recommendation that anti-malarial drugs should be prescribed for only patients with positive MRDT (or microscopy) results.…”
Section: Discussionmentioning
confidence: 90%